Pengembangan Spatial Literacy Untuk Meningkatkan Pembelajaran Geografi Di Sekolah Dasar - Raden Adinda Zalfa; Rizka Putri Ayuning; Rustini, Tin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Spatial intelligence or spatial literacy is one of the pillars of geographic intelligence. At every level of education there are various ways to develop innovative geography learning, especially at the elementary school level. However, not all developments in geography learning involve spatial literacy as one of the pillars of geographic intelligence. This research is motivated by the ability of elementary school students in studying geography material. This study aims to provide various recommendations for developing spatial literacy in elementary schools in relation to learning geography. The method used in this study is a literature study, namely by reviewing relevant previous research studies and making conclusions based on the results obtained. The literature selection process is carried out by 4 procedures according to Taylor. The results of this study describe that the development of spatial literacy needs to be accompanied by models and learning media that support each other so as to achieve maximum development